HAS THE IMPLEMENTATION OF ACCRUAL ACCOUNTING IN INDONESIA BEEN SUCCESSFUL? A LITERATURE REVIEW - Prayudi, Made Aristia; Paradila, I Made Pradnyana; Dananjaya, I Gusti Ngurah Agung; Adnyana, I Dewa Gede Anom Jambe (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This paper examines the implementation of accrual accounting in government organizations in Indonesia. It discusses the challenges and success factors related to the adoption of accrual accounting as part of the government accounting reform initiatives. The topic is significant as it sheds light on the progress and barriers faced by Indonesia in fully adopting accrual accounting, an important component of public sector financial management. The problem addressed in this paper is the low level of adoption of accrual accounting in Indonesian government organizations and the challenges encountered during its implementation. The research question is: How successful has the implementation of accrual accounting been in Indonesian government organizations, and what are the barriers to its adoption? This paper provides a unique contribution by investigating both the adoption process and the empirical findings related to the success of accrual accounting in Indonesia, an area that has not been comprehensively studied. Previous research has often overlooked the specific challenges faced in Indonesia, and this study fills that gap by offering an in-depth review of the issues related to the practical application of accrual accounting in the public sector. A literature review was conducted, examining both theoretical frameworks and empirical studies on the implementation of accrual accounting in Indonesia. This study synthesizes research on the adoption process, highlighting key barriers and success factors identified in previous studies. The study reveals that the adoption of accrual accounting in Indonesia remains relatively low, with effectiveness being limited. Challenges such as resistance to change, inadequate capacity, and institutional constraints were found to impede the full implementation of accrual accounting in government organizations. The study concludes that while the adoption of accrual accounting in Indonesia is still in its early stages, there are significant barriers to its effective implementation. The findings suggest that for successful implementation, policy adjustments and capacity-building measures are crucial. The main takeaway is that a more strategic approach is needed to overcome the institutional and practical challenges in adopting accrual-based accounting standards in Indonesia.